VITEK2 BASED DIAGNOSIS AND CHARACTERIZATION STAPHYLOCOCCI AERUS STRAIN CAUSING URINARY TRACT INFECATION IN FEMAL AND MALE - Jaber, Salim Abdul Amir (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Background, The aim of this study was to assess the clinical presentation, risk factors, and comorbidities of the patients with Staphylococcus aureus bacteriuria, and to analyze the antimicrobial susceptibility data of S. aureus isolated from their urine samples. Methods, A total of 80 isolates of S. aureus were collected from patients with urinary tract infections (UTIs)in hospital Refai. Urinalysis was performed manually, including macroscopic examination of color and appearance, and microscopic examination for the presence of urinary pus cells, and bacteria and culture on MaCconky agar,Blood agar. Full diagnosis and susceptibility testing of S. aureus were performed by the VITEK 2 system (BioMérieux, Marcy-l'Étoile, France) using standard criteria. Results, The majority of the patients were female (50), with a mean age of 30 years and male(30) mean ageof45 years . Most of the patients were inhospatial . Seventy positive urine cultures were associated with UTI symptoms. ButTen negative urine cultures. Conclusion, Although S. aureus UTI is known to be associated with other risk factors such as urinary catheterization, long hospital stay, or complicated UTI, our results show the community-acquired presentation of UTI. Trimethoprim-sulfamethoxazole may be used as an effective treatment for UTI caused by S. aureus. S. aureus UTI could be an alarming sign of more invasive infections such as S. aureus bacteremia, though clinical evaluation and finding the source of S. aureus are crucial for effective treatment and prevention of further complications